Grover Cleveland papers - Cleveland, Grover, 1837-1908.
Correspondence, diaries, messages to Congress, speeches, writings, printed matter, and other papers relating chiefly to Cleveland's first presidential administration. Subjects also include Cleveland's second presidential administration, presidential elections, and Democratic Party politics.
Correspondents include John Peter Altgeld, Chester Alan Arthur, Thomas F. Bayard, Erastus Cornelius Benedict, Wilson Shannon Bissell, John Griffin Carlisle, Joseph Hodges Choate, George William Curtis, Donald McDonald Dickinson, Sanford B. Dole, William Crowninshield Endicott, Robley D. Evans, Melville Weston Fuller, Richard Watson Gilder, Walter Quintin Gresham, Charles Hamlin, Judson Harmon, Benjamin Harrison, Abram S. Hewitt, David B. Hill, Joseph Jefferson, L.Q.C. Lamar, Daniel Scott Lamont, Daniel Manning, Richard Olney, Alton B. Parker, Terence Vincent Powderly, William Gorham Rice, Theodore Roosevelt, Horatio Seymour, Edward Morse Shepard, Hoke Smith, Oscar S. Straus, Henry Watterson, James B. Weaver, and William C. Whitney.
Microfilm edition of Series 1-9G available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
President of the United States, governor of New York, and lawyer. Full name: Steven Grover Cleveland.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Altgeld, John Peter, -- 1847-1902 -- Correspondence; Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Bayard, Thomas F. -- 1828-1898 -- Correspondence; Benedict, Erastus Cornelius, -- 1800-1880 -- Correspondence; Bissell, Wilson Shannon, -- 1847-1903 -- Correspondence; Carlisle, John Griffin, -- 1835-1910 -- Correspondence; Choate, Joseph Hodges, -- 1832-1917 -- Correspondence; Curtis, George William, -- 1824-1892 -- Correspondence; Dickinson, Donald McDonald, -- 1846-1917 -- Correspondence; Dole, Sanford B. -- 1844-1926 -- Correspondence; Endicott, William Crowninshield, -- 1826-1900 -- Correspondence; Evans, Robley D. -- 1846-1912 -- Correspondence; Fuller, Melville Weston, -- 1833-1910 -- Correspondence; Gilder, Richard Watson, -- 1844-1909 -- Correspondence; Gresham, Walter Quintin, -- 1832-1895 -- Correspondence; Hamlin, Charles, -- 1861-1938 -- Correspondence; Harmon, Judson, -- 1846-1927 -- Correspondence; Harrison, Benjamin, -- 1833-1901 -- Correspondence; Hewitt, Abram S. -- 1822-1903 -- Correspondence; Hill, David B. -- 1843-1910 -- Correspondence; Jefferson, Joseph, -- 1829-1905 -- Correspondence; Lamar, L. Q. C. -- 1825-1893 -- Correspondence; Lamont, Daniel Scott, -- 1851-1905 -- Correspondence; Manning, Daniel, -- 1831-1887 -- Correspondence; Olney, Richard, -- 1835-1917 -- Correspondence; Parker, Alton B. -- 1852-1926 -- Correspondence; Powderly, Terence Vincent, -- 1849-1924 -- Correspondence; Rice, William Gorham, -- 1856-1945 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Seymour, Horatio, -- 1810-1886 -- Correspondence; Shepard, Edward Morse, -- 1850-1911 -- Correspondence; Smith, Hoke, -- 1855-1931 -- Correspondence; Straus, Oscar S. -- 1850-1926 -- Correspondence; Watterson, Henry, -- 1840-1921 -- Correspondence; Weaver, James B. -- 1833-1912 -- Correspondence; Whitney, William C. -- 1841-1904 -- Correspondence; Democratic Party (U.S.); Presidents -- United States -- Election; United States -- History -- 1865-1921.; United States -- Politics and government -- 1865-1933.; United States -- Politics and government -- 1885-1889.; United States -- Politics and government -- 1893-1897.; Governors -- New York (State).; Lawyers; Presidents -- United States